Mengukur Indeks Kemaslahatan BPRS Amanah Ummah Bogor - Dedi Junaedi; Sri Hayatin Nufus (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2019)
Islamic financial institutions, especially Islamic banking, should, not only be assessed from the high and low value of profitability such as conventional banking. LKS can also provide reasonable benefits or a real benefit index to the surrounding public. So, assessing the performance of Islamic banking cannot be equated with conventional banking considering that both have different goals and views. Islamic Maqashid, namely the realization of benefit - in safeguarding religion, soul, mind, descent, and property - should be considered in measuring the performance of a Sharia financial institution. The purpose of this study pioneered an effort to measure the welfare index of BPRS Amanah Umat by approaching the issue of religion, soul, mind, lineage, and wealth in the BPRS Amanah Ummah. This study uses a combination of qualitative descriptive research and quantitative analysis with research subjects from two parties, internal parties (employees) and external parties (customers) BPRS mandate Ummah. The object of research from this study is the five elements of the approach to maslahah dharuriyah. The method of data collection consists of methods of observation, questionnaires, documentation, and literature. The data validity technique uses qualitative descriptive testing, enriched with statistically processed data with analysis comparing the mean with the independent test sample t-test. The results of the study concluded that the highest value of the welfare index of the BPRS Amanah Ummah is the reason with an average value of 4.3 and the lowest value of maslahah is the maslahah descent with an average value of 3.9. Based on quantitative analysis, the overall index of the five elements of maslahah is 0.8364 (83.64%), with reason in the first place and maslahah descendants in fifth place. The quantative analysis shows that there are significant differences between the perceptions of internal and external parties. Differences in perceptions of the value of benefit are influenced by factors in the number of dependents, differences in age, gender, and level of education.